2013
DOI: 10.1016/j.jad.2012.05.064
|View full text |Cite
|
Sign up to set email alerts
|

Does executive functioning (EF) predict depression in clinic-referred adults?: EF tests vs. rating scales

Abstract: Background Deficits in executive functioning (EF) are implicated in neurobiological and cognitive-processing theories of depression. EF deficits are also associated with Attention-deficit/hyperactivity disorder (ADHD) in adults, who are also at increased risk for depressive disorders. Given debate about the ecological validity of laboratory measures of EF, we investigated the relationship between depression diagnoses and symptoms and EF as measured by both rating scales and tests in a sample of adults referred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 49 publications
3
19
0
1
Order By: Relevance
“…This absence of a strong correlation between ratings and tests reflects a lack of ecological validity of neuropsychological tests. Other studies using the BDEFS English Version have shown similar results [17][18][19][20]24,25 . For example, as found by Vasconcelos et al 26 the BIS 11 Brazilian Portuguese Version presents almost non-significant correlations with the Iowa Gambling Task, which support the theoretical and statistical difference between these types of neuropsychological methods.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…This absence of a strong correlation between ratings and tests reflects a lack of ecological validity of neuropsychological tests. Other studies using the BDEFS English Version have shown similar results [17][18][19][20]24,25 . For example, as found by Vasconcelos et al 26 the BIS 11 Brazilian Portuguese Version presents almost non-significant correlations with the Iowa Gambling Task, which support the theoretical and statistical difference between these types of neuropsychological methods.…”
Section: Discussionsupporting
confidence: 66%
“…Knouse 25 used the BDEFS successfully to examine the relationship of EF to understand and predict the mediation of self-regulation in academic performance. That study 19 also showed that the BDEFS could be used to predict depressive symptoms, especially using the self-management of time, self-organization, and problem-solving subscales, in a sample with symptoms of ADHD and depression. Future studies should address the relationship between the Brazilian adaptation of BDEFS and functional outcomes in a Brazilian context.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Similarly, executive functioning deficits have emerged as a risk factor for depressive symptoms in clinical and community samples (Feldman, Knouse, & Robinson, 2013; Knouse, Barkley, & Murphy, 2013; Wingo, Kalkut, Tuminello, Ascnape, & Han, 2013). Thus, negative impact of stress on executive functioning may be a plausible mediating mechanism linking stress exposure to levels of depression among maternal caregivers of adolescent or adult children with developmental disabilities.…”
Section: Executive Functioning Limitations As a Mediatormentioning
confidence: 99%